EFFECTIVENESS OF LAND-BASED AND AQUATIC PHYSICAL EXERCISE ON PHYSICAL FITNESS, DEPRESSION STATUS AND QUALITY OF LIFE IN DIABETES MELLITUS TYPE 2 - Fajriyah, Novita; Arifin, Hidayat; Rohmah, Ulfa Nur (SYNTIFIC, 2023)
Background. Type 2 Diabetes Mellitus is a chronic disease that can exacerbate depressive symptoms due to increased symptom burden complications that lead to functional impairment and decreased quality of life. People with T2DM are twice as likely to experience loss of physical function, and decreased physical fitness and strength than people without T2DM. Physical effort is an integral part of programs for disease prevention and management. Physical fitness, depression status, and quality of life have not been specifically evaluated and described after training in these two environments. This article aims to find and review land and water-based physical exercise intervention research as an alternative solution to improve physical fitness, depression status, and quality of life of T2DM patients. Research Method. Descriptive analysis method. Systematic reviews were evaluated using the PRISMA checklist. Database: Scopus, Science direct, Pubmed, CINAHL, and ProQuest. Article search with the PICOS framework. The Joanna Briggs Institute (JBI) Critical Appraisal as an alternative to assessing the risk of study bias. Findings. The 25 articles that met the inclusion criteria consisted of 18 (Randomized Control Trials) and 7 (Quasy-experiments). Consisting of land and water-based aerobic classifications that are useful in the physical and psychological aspects of T2DM. Conclusion. There is an influence of land-based and aquatic physical exercise on physical fitness, depressive status, and quality of life in T2DM patients.